A Potential Role of MicroRNA in the Renal Cancer and Its Tumor Microenvironment - Daniel Chikere Ali; Siva Bharath Merugu (Annals of Urologic Oncology)
Renal cell carcinoma (RCC) accounts for approximately 2.2% of all diagnosed cancers and 1.8% of cancer-related deaths. Clear cell renal cell carcinoma (ccRCC) is the most prevalent subtype of RCC, accounting for approximately 70–80% of all cases. Despite significant advancements in therapeutic strategies over recent decades, treatment outcomes for ccRCC patients remain suboptimal. Prognosis for individuals with advanced or metastatic ccRCC continues to be poor, with a 5-year survival rate below 10%. This is largely due to the intricate and heterogeneous nature of the tumor microenvironment (TME). Current biomarkers and screening techniques for RCC often lack sensitivity or are cost-prohibitive, highlighting the need for novel biomarkers that enable early detection, particularly in high-risk populations. MicroRNAs (miRNAs) exhibit unique properties that make them promising candidates for cancer biomarker development. Researchers have analyzed miRNA expression profiles in biological samples from RCC patients, identifying specific circulatory or urinary miRNAs as potential diagnostic or follow-up markers. Additionally, the expression patterns of certain miRNAs have been linked to patient responses to chemotherapy, immunotherapy, and targeted treatments such as sunitinib. This study reviews existing research on the role of miRNAs in RCC, including their potential as biomarkers, therapeutic targets, and regulators of treatment response in affected patients.